2020
DOI: 10.1044/2020_jslhr-19-00335
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic Complexity as a Linguistic Marker to Differentiate Mild Cognitive Impairment From Normal Aging

Abstract: Purpose In this study, we sought to identify critical linguistic markers that can differentiate sentence processing of individuals with mild cognitive impairment (MCI) from the sentence processing of normal-aging populations by manipulating sentences' linguistic complexity. We investigated whether passive sentences, as linguistically complex structures, can serve as linguistic markers that can contribute to diagnoses that distinguish MCI from normal aging. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 63 publications
4
13
0
1
Order By: Relevance
“…As delineated in the methods on the passivization process of Korean, the NP movement occurs from its original place as in the object position to the subject position in its surface structure, although the thematic role of the moved NP represents a theme, which is not canonically placed in a subject position. Sung et al (2020) confirmed that individuals with MCI behaviorally demonstrated greater difficulties in the syntactic structures that are claimed to be theoretically more complex. Furthermore, the authors tested the models to elicit the most efficient combination of the subtests among three models: (1) only active sentences, (2) only passive sentences, and (3) both active and passive sentences.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…As delineated in the methods on the passivization process of Korean, the NP movement occurs from its original place as in the object position to the subject position in its surface structure, although the thematic role of the moved NP represents a theme, which is not canonically placed in a subject position. Sung et al (2020) confirmed that individuals with MCI behaviorally demonstrated greater difficulties in the syntactic structures that are claimed to be theoretically more complex. Furthermore, the authors tested the models to elicit the most efficient combination of the subtests among three models: (1) only active sentences, (2) only passive sentences, and (3) both active and passive sentences.…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore, the current test has been validated through a series of the preliminary studies by Sung and colleagues by comparing young and old groups (Sung, 2015a,b;Sung et al, 2017). A most recent research on the SAB suggested that the syntactic complexity serves as a critical linguistic marker for differential diagnosis of mild cognitive impairment (MCI) from normal aging populations (Sung et al, 2020). The authors reported that individuals with MCI did not significantly differ from normal elderly adults in a simple active syntactic form, whereas they performed significantly worse on the passive sentences, which are linguistically more complex and challenging to process than active sentences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sentence complexity could also affect speech performance in various disorders, such as stuttering, and in those with degrading capacities, such as in the elderly population [30]. Individuals with mild cognitive impairment experienced greater difficulties in processing passive structures of sentence comprehension compared to those in the unimpaired cognitive group [33]. The morphosyntax of Malay lan-guage is predominantly derivational and it is characterized by an interchangeable mix of lexical and grammatical elements.…”
Section: Introductionmentioning
confidence: 99%
“…Current research in speech production and its disorders has mainly focused on speech and language separately [35]. Although previous studies have confirmed that linguistic factors affect speech motor coordination [31][32][33], relatively few investigators have examined how language demands may influence the production of speech, especially using a dual-task paradigm. To our knowledge, none of these studies have been conducted among Malay speakers, making it an issue when diagnosing a clinical population.…”
Section: Introductionmentioning
confidence: 99%